Comparison of Autistic Traits Between Iranian Students With Different Ethnic Backgrounds: A Cross-Cultural Study - Elhami Athar, Mojtaba; Ebrahimi, Ali; Karimi, Sirvan; Esmailzadeh, Roya; Mousavi Asl, Esmaeil; Azizi, Morteza; Heidarzadeh, Saman; Siahkamari, Esfandiar; Sharifi, Amin; Ramezani Farani, Abbas (Frontiers in Psychiatry, 2021)
Autistic traits (ATs) include symptoms associated with autism spectrum conditions (ASCs), which are assumed to be continuously distributed across the general population. Studies have indicated the cultural differences in the expression of ATs. Notwithstanding, our literature review indicated that studies on cross-cultural differences in the expression of ATs included samples from different countries. This is the first study designed to compare the expression of ATs between different ethnicities from the same country. Using the Autism-spectrum Quotient (AQ-28), we examined the possible cultural differences in the expression of autistic traits from four groups of students with different ethnic backgrounds, including Turkish (n = 262), Persian (n = 290), Kurdish (n = 300), and Luri (n = 307) students. Behaviors associated with autistic traits were reported overall higher for males than females. Also, significant cultural differences in autistic traits were found that were different for males and females. Furthermore, while the medical sciences student group scored significantly higher than the humanities group in the Imagination dimension, the humanities group had significantly higher scores in Number/Pattern dimensions than the engineering and medical sciences groups. Altogether, our results provide further support for the idea that the expression of ATs is significantly influenced by culture. A significant limitation of the current study was that groups were not matched with respect to age, percentage of male participants, and fields of studies, and that these variables may influence the AQ scores.